Improving dementia care: The role of screening and detection of cognitive impairment. Issue 2 (1st February 2013) - Borson, Soo; Frank, Lori; Bayley, Peter J.; Boustani, Malaz; Dean, Marge; Lin, Pei‐Jung; McCarten, J. Riley; Morris, John C.; Salmon, David P.; Schmitt, Frederick A.; Stefanacci, Richard G.; Mendiondo, Marta S.; et al.
Abstract : The value of screening for cognitive impairment, including dementia and Alzheimer's disease, has been debated for decades. Recent research on causes of and treatments for cognitive impairment has converged to challenge previous thinking about screening for cognitive impairment. Consequently, changes have occurred in health care policies and priorities, including the establishment of the annual wellness visit, which requires detection of any cognitive impairment for Medicare enrollees. In response to these changes, the Alzheimer's Foundation of America and the Alzheimer's Drug Discovery Foundation convened a workgroup to review evidence for screening implementation and to evaluate the implications of routine dementia detection for health care redesign. The primary domains reviewed were consideration of the benefits, harms, and impact of cognitive screening on health care quality. In conference, the workgroup developed 10 recommendations for realizing the national policy goals of early detection as the first step in improving clinical care and ensuring proactive, patient‐centered management of dementia.